The Concept Of Self Healing For Children In Islamic Education (Perspective Of The Qur'an And Hadits) - Raihanah Raihanah (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2023)
Recently, mental health has been frequently discussed because the number of mental disorders in Indonesia has increased significantly in each period. Considering that alternative medicine is rarely used due to the rapid development of the times, this research has the aim of opening up people's thinking about alternative medicine, one of which is the Al-Qur'an. This research is a library research by analyzing several sources such as books, scientific articles and others. The independent variable in this study is self-healing, while the dependent variable is self-healing from the perspective of the Qur'an and Hadith.In the span of 14 centuries, healing with the Qur'an has become something that is well known to Muslims. They treat all diseases with the Qur'an because they believe in the word of Allah SWT related to healing. In fact, onIn a history it is explained that the Prophet Muhammad once did ruqyah himself when he was sick by reading the letter al-Mu'awwidhatain, namely the letter al-Falaq and the letter an-Nas. Further research can be carried out by studying several surahs, certain verses which are believed by Muslims to be very effective medicines for various diseases, especially mental illnesses